IMPACT OF THE WAR ON INTERNATIONAL TRANSPORT OF UKRAINE - KHARUN, Olena; HRYTSYNA, Lesia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article found that the full-scale war in Ukraine had a strong impact on international transportation. The structure of the volume of cargo transportation and the number of transported passengers were analyzed. It was determined that there is uncertainty in the market of international freight transportation of Ukraine during the studied period. On the one hand, the war had a negative impact on the country’s economy and led to a decrease in the volume of cargo transportation. On the other hand, Ukraine is an important transit country through which key logistics routes connecting Europe and Asia pass. It was established that the blocking of air transport and sea trade, with the exception of the "Grain Initiative", led to a radical change in the structure of domestic import/export and the leadership of land corridors. Global transformations in world trade caused by the war in Ukraine also affected the configuration of existing supply chains, Ukrainian exports were completely reoriented towards the EU. It is indicated that Ukraine’s signing of an agreement on visa-free transport cooperation with the European Union has opened up new prospects for bilateral international road transport, freeing Ukrainian carriers from the need to obtain permits for flights to EU countries. However, there are also negative trends that affect the growth of transport services and, as a result, decrease the competitiveness of transport companies. A list of legislative and regulatory innovations and organizational measures aimed at improving international transportation is given. It is argued that a successful solution for the recovery of the country will be the integration of the Ukrainian economy into the EU economic system with the help of various European logistics and infrastructure projects. It was determined that the key factors in the normalization of transportation were: the conclusion of the "Grain Initiative" with the UN and Turkey, which allowed to unblock the ports of Great Odesa; signing the Agreement on the Liberalization of Road Freight Transportation with the EU; development of border infrastructure, in particular, increasing the capacity of existing road and railway checkpoints, as well as the opening of new ones; increasing cargo handling in the ports of the Danube port cluster.